An investigation into the effects of grievance and its management procedures in Senior High Schools in the Okwahu East District. - Ampong, Grace Ama (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirement For The Degree Of Master Of Public Administration.